Eksplorasi Peran dan Tantangan Visual Jockey Pada Merdeka Fest 2024 - Linggih, I Kadek Dwi Krisna Anugrah; Sumadi, I Gede Sumadi; Asmarani, I Gusti Ayu Ratih (Journal of Event and Convention Management, 2025)
The Indonesian music festival industry has rapidly grown, encouraging the use of visual elements to enhance audience experience. Visual Jockeys (VJs) play an important role in creating an atmosphere that supports musical performances. This study aims to explore the VJs' contribution to audience experience and identify challenges faced in music festivals. This research adopts a descriptive qualitative approach, collecting data through observation, semi-structured interviews with the Founder, Creative Director, and VJ of Tjiwa Creative, and festival documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing based on the Five Aspects of Event Experience (Getz & Page, 2016). The results show that VJs contribute to creating immersive multisensory experiences, strengthening audience engagement, and building event identity. Challenges include real- time visual synchronization, production coordination, and the use of cutting-edge visual technology. The findings highlight the importance of strategic visual planning in the success of music festivals.